Factors Associated with Maternal Anemia and its Relationship with a Low Birth Weight of Newborn - Shahzad Rauf, Shamayal Mandokhel, Hina Pirzada, Rehman Sher, Munema Shakeel, Farhatullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine maternal anemia and its relationship with the nutritional status and low birth weight of a newborn. Study Design: Cross-sectional analytical study. Place and Duration of Study: Tertiary Care Hospital KPK Peshawar from 1st January 2022 to 30th June 2022. Methodology: Three hundred and eighty five individuals, aged between 18 to 45 years were enrolled. All patients with hemoglobin level <11 g/dl, low birth and normal were included. Patients with a history of hypertension and diabetes mellitus were excluded. Results: The maternal anemia was found in 39.37% while low birth weight was among 16.62% result was significant (P=0.00). Mothers taking a balanced diet and milk regularly were reported with normal hemoglobin. Low birth weight was reported in multigravida 28.3% and 20.25% in primigravida. The multiparous give birth to 29.09% low birth weight and patients taking a gap of less than 2 years have a low birth weight of a newborn and he results were significant at P=0.043. Conclusion: The maternal anemia can be a risk factor for the low birth weight of the newborn. Keywords: Maternal anemia, Nutrition, Newborn, Deficiencies, Low birth weight